The Credit Card Debt Puzzle and Noncognitive Ability - Choi, Hwan-sik; Laschever, Ron A (Review of Finance, 2018)
Abstract Many households concurrently hold low-yield liquid assets while incurring costly credit card debt. In our sample, more than 80% of households with credit card debt also have low-yield liquid assets. Using data from the Health and Retirement Study (N = 30,517), we examine the role of noncognitive skills as well as the economic, financial, and demographic factors that affect the likelihood of co-holding. We find that the “Big Five” personality traits have a statistically significant and economically important effect: households with a more agreeable, introvert, and less conscientious head of household are more likely to co-hold. We also examine the role of intra-household dynamics.